Repercusión en la libre elección de contribuyentes, sector servicios al abrir cuenta de detracciones – Banco de la Nación, Trujillo - Heredia Valderrama, Diego Jesús (2019)
This investigation tries to resolve the question of whether the Taxpayer is being violated their Right to Free Choice by forcing them to open their Withdrawal Current Account only in the National bank, not allowing them in any other Bank of the Financial System. For this research, the Historical Method was applied, as well as the Bibliographic Research and Documentary Analysis techniques, obtaining as results that Legislative Decree No. 940 is the only norm that obliges the Taxpayer to open the Current Account of Withdrawals only in the Bank of the Nation, likewise said norm contradicts the Main norm that is the Magna Carta of Peru (The Constitution) which in its article Nº 2 defends the Right to Free Choice. The results also show that the benefits provided by the National bank are null and that it has some disadvantages compared to the Current Accounts provided by the other Banks of the Financial System. In conclusion, forcing Taxpayers to open the Withdrawal Current Account only in the National bank is violating their Right to Free Choice, a right that is recognized in the Magna Carta of Peru (The Constitution), as well as well as in the Civil Code and in the Consumer Protection and Defense Law.